EPISOME-MEDIATED TRANSFER OF DRUG RESISTANCE IN ENTEROBACTERIACEAE VIII. : Six-Drug-Resistance R Factor - Watanabe, Tsutomu (1964)
Watanabe, Tsutomu (Keio University School of Medicine, Tokyo, Japan), Chizuko Ogata, and Sachiko Sato. Episome-mediated transfer of drug resistance in Enterobacteriaceae. VIII. Six-drug-resistance R factor. J. Bacteriol. 88:922–928. 1964.—The multiple-drug-resistant Escherichia coli strain isolated by Lebek in 1963 was found to transfer resistance to sulfonamide, streptomycin, chloramphenicol, tetracycline, kanamycin, and neomycin together by conjugation, as well as by transduction with phage P1kc, suggesting that these drug-resistance markers are carried by a single R factor (R(6)). The results of transductional and spontaneous segregations of the drug-resistance markers of R(6) have shown that R(6) has independent genetic determinants for sulfonamide, streptomycin, chloramphenicol, tetracycline, and kanamycin-neomycin resistance. Resistance to kanamycin and neomycin is probably controlled by a single gene, because no segregation was observed between these two. The resistance transfer factor of R(6) was found to be of the fi(+) type.